Inkonsistensi Kedaulatan Rakyat dalam Undang-Undang Dasar Negara Republik Indonesia Tahun 1945 - Budiman NPD Sinaga (Kanun Jurnal Ilmu Hukum, 2013)
ABSTRACT: During the preparation of Indonesian independence, the founding fathers designed a Constitution. Constitution was later known as the 1945 Constitution of the Republic of Indonesia. The Constitution embraces of sovereignty of the people. To overcome the shortcomings of the Constitution, it has been madeseveral changes. However, changes were turned out inconsistent with existing regulations, such as the regulation of representative democracy and direct democracy. To address the inconsistencies, it then needs to be revised more as there are various provisions of the Constitution that are inconsistent with aforementioned matters. Inconsistency of People Sovereignity in the Constitution 1945 of the Republic of Indonesia